A Fully Integrated Wireless SoC for Motor Function Recovery After Spinal Cord Injury - Yi‐Kai Lo; Yen‐Cheng Kuan; Stanislav Culaclii; Brian Kim; Po‐Min Wang; Chih-Wei Chang; Jonathan Massachi; Minji Zhu; Kuan‐Fu Chen; Parag Gad; V. Reggie Edgerton; Wentai Liu (2017)
This paper presents a wirelessly powered, fully integrated system-on-a-chip (SoC) supporting 160-channel stimulation, 16-channel recording, and 48-channel bio-impedance characterization to enable partial motor function recovery through epidural spinal cord electrical stimulation. A wireless transceiver is designed to support quasi full-duplex data telemetry at a data rate of 2 Mb/s. Furthermore, a unique in situ bio-impedance characterization scheme based on time-domain analysis is implemented to derive the Randles cell electrode model of the electrode-electrolyte interface. The SoC supports concurrent stimulation and recording while the high-density stimulator array meets an output compliance voltage of up to ±10 V with versatile stimulus programmability. The SoC consumes 18 mW and occupies a chip area of 5.7 mm × 4.4 mm using 0.18 μm high-voltage CMOS process. In our in vivo rodent experiment, the SoC is used to perform wireless recording of EMG responses while stimulation is applied to enable the standing and stepping of a paralyzed rat. To facilitate the system integration, a novel thin film polymer packaging technique is developed to provide a heterogeneous integration of the SoC, coils, discrete components, and high-density flexible electrode array, resulting in a miniaturized prototype implant with a weight and form factor of 0.7 g and 0.5 cm